(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This study examined the effect of sustainable servicescape quality on patron satisfaction in cinemas in Port Harcourt, Rivers State, Nigeria. Specifically, the study investigated the influence of ambient conditions, spatial layout and functionality, signage and symbols, and cleanliness on patron satisfaction. A quantitative research design employing a descriptive survey approach was adopted. Data were collected from 210 cinema patrons using a structured questionnaire measured on a 5-point Likert scale. Descriptive statistics and Pearson Product Moment Correlation were used to analyze the data at a 5% level of significance. The findings revealed significant positive relationships between all four servicescape dimensions and patron satisfaction: ambient conditions (r = 0.481, p < 0.05), spatial layout and functionality (r = 0.519, p < 0.05), signage and symbols (r = 0.443, p < 0.05), and cleanliness (r = 0.574, p < 0.05). The results further indicated that cleanliness exerts the strongest influence on patron satisfaction, explaining 33% of its variance. The study concludes that sustainable servicescape quality is a critical determinant of patron satisfaction and recommends that cinema operators in Port Harcourt prioritize environment-conscious service design to enhance customer loyalty and long-term operational viability.